A) 2/3 * (2 5/6 + 1,75) =
b)(4 7/8 - 2,5) * 1 1/3=
c)2 2/3 : (1 7/9 + 2 2/15)
d)0,3 * 3 3/8 - 2,25 * 3/10 + 6/20 * 8 7/8=
e)1 2/3 + 2 3/4 + 3 4/5 *(8 2/5 - 7 3/20) =
f) 2,3 - (1 3/4 - 6,5 * 1/6)
_____________________ =
3 2/3 - 2/3 : 2 1/6 + 4/13

Plx na jutro !!! rozwiązujcie ;]

3

Odpowiedzi

2009-09-27T21:00:56+02:00
A) =2/3*(17/6+175/100)=2/3*21/12=7/6=1 1/6
b)=(39/8-25/10)*1 1/3=(390/80-200/80)*1 1/3=190/80*! 1/3=190/80*4/3=190/60=3 1/6
2009-09-27T21:05:07+02:00
A) 2\3 x (17\6 +7\4)= 2\3 (34\12 + 31\12)= 2\3 x 1054\12 = 4\12 + 1054\12= 1058\12 = 88\12
2009-09-27T21:10:23+02:00
A) ⅔ * (17:6 + 7:4) = ⅔ * (34:12 + 21:12) = ⅔ * (55:12) = 110:36 = 3+1:18
b)(39:8 - 25:10) * 4:3 = (390:80 - 200:80) * 4:3 = (190:80) * (4:3) =
= 190:60 = 3 + ⅙
c)8:3 : (16:9 + 32:15) = 8:3 : (160:90 + 192:90) = 8:3 : 352:90 = 30:44
d)0,3 * 3 3/8 - 2,25 * 3/10 + 6/20 * 8 7/8 = (3:10) * (27:8) - (9:4 * 3:10) + (6:20 * 71:8)= 81:80 - 27:40 + 213:80) = 81:80 - 54:80 + 213:80 = 240:80 = 3
e) 5:3 + 11:4 + 19:5*(42:5 - 143:20) = 20:12 + 33:12 + 19:5*(168:20 - 143:20) = 53:12 + 19:5 * 25:20 = 53:12 + 76:20 = 265:60 + 228:60 = 493:60 = 8+16:60
F)23:10 - (7:4 - 65:10 * 1:6)=32:10 - 7:4 + 65:10 * 1:6= 7:4 + 195:30 * 5:30 = 7:4 + 975:30 = 210:120 + 3900:120 = 4110:120 = 34+¼
3 2/3 - 2/3 : 2 1/6 + 4/13 = 11:3 - 2:3 : 13:6 = 11:3 - 2:3 * 6:13 = 11:3 - 4:13 = 143:26 - 8:26 = 135:26 = 5+5:26
137:4 : (135:26) = 137:4 * (26:135) = 3562:540=6+322:540